Flavin-Helicene Amphiphilic Hybrids: Synthesis, Characterization, and Preparation of Surface-Supported Films - Jakubec, Martin; Novák, David; Zatloukalová, Martina; Císařová, Ivana; Cibulka, Radek; Favereau, Ludovic; Crassous, Jeanne; Cytryniak, Adrianna; Bilewicz, Renata; Hrbáč, Jan; Storch, Jan; Žádný, Jaroslav; et al. (ChemPlusChem, 2021)
This work reports on the preparation and structural characterization of flavo[7]helicene 1 (flavin-[7]helicene conjugate), which was subsequently characterized at the molecular level in either an aqueous environment or an organic phase, at the supramolecular level in the form of polymeric layers, and also embedded in a lipidic mesophase environment to study the resulting properties of such a hybrid relative to its parent molecules. The flavin benzo[g]pteridin-2,4-dione (isoalloxazine) was selected for conjugation because of its photoactivity and reversible redox behavior. Compound 1 was prepared from 2-nitroso[6]helicene and 6-methylamino-3-methyluracil, and characterized using common structural and spectroscopic tools: circular dichroism (CD), circularly polarized luminescence (CPL) spectroscopy, cyclic voltammetry (CV), and DFT quantum calculations. In addition, a methodology that allows the loading of 1 enantiomers into an internally nanostructured lipid (1-monoolein) matrix was developed.
Keywords: thin layers; helicenes; redox behavior; flavins; lipidic cubic phases